LA-ICP-MS zircon and monazite U-Pb data for the key lithological units in the Chonghuer-Jiadengyu region of the Chinese Altai - Lingzhu Kong; Yingde Jiang; Karel Schulmann; Zhang Jian (PANGAEA, 2022)
Identification of advancing and retreating modes in fossil orogenic belts is not always straightforward. Such issue is addressed in the submitted paper via the case study of the northwestern Chinese Altai where the suprasubduction structures are well preserved. Combined with detailed mapping, structural/petrological observations, seven samples were collected from the key lithological units of Jiadengyu and Chonghuer region in the Xinjiang Uygur Autonomous Region for zircon and monazite U-Pb dating to provide critical geochronological constraints on the individual deformational episodes, including two zircon samples (19CA36 and 17CA105-7) and five monazite samples (17CA107, 17CA105-4, 19CA41, 19CA45-1, and 19CA45-3). Migmatite samples 19CA41 and 17CA107 are characterized by sub-horizontal S1 foliations associated with extensional shear bands. Sample 19CA45-1 collected from the migmatitic Habahe Group domain shows nearly complete transposition of S1 foliation by S2 fabric. Samples 19CA36 and 19CA105-7 were collected from syn-D2 granite intrusions. Leucogranite dyke (sample 17CA105-4) and pegmatite (sample 19CA45-3) were emplaced as tensional fractures that formed in response to D2 shortening. Zircon and monazite grains were separated after rock crushing using conventional heavy liquid and magnetic properties and then selected under a binocular microscope. These grains were mounted in epoxy resin, polished to approximately one-third of their thickness. U-Pb dating of zircon and monazite were analyzed by LA-ICP-MS at the Wuhan SampleSolution Analytical Technology Co., Ltd. U-Pb dating of zircon samples were conducted by a COMPexPro 102 ArF excimer laser and a MicroLas optical system coupled with an Agilent 7700e ICP-MS. Most analyses were performed with a beam diameter and frequency of 32 μm and 5 Hz. GJ-1 standard zircon was also determined for monitoring the accuracy of U-Pb dating. Zircon 91500 was used as an external standard for U-Pb dating calibration. U-Pb dating of monazite samples was performed using the same operating processes and instruments. In this work, the spot size and frequency of the laser were set to 16 μm and 2 Hz, respectively. Monazite standard 44069 was used as an external standard for U-Pb dating. Monazite standard Trebilcock was used as a secondary standard to assess the accuracy of analyses. Each analysis of zircon/monazite was performed using a background acquisition of approximately 25 s followed by 65 s of data acquisition.